Role of endothelium-pericyte signaling in capillary blood flow response to neuronal activity. Issue 8 (August 2021) - Zhang, Wenri; Davis, Catherine M; Zeppenfeld, Douglas M; Golgotiu, Kirsti; Wang, Marie X; Haveliwala, Mariya; Hong, Daniel; Li, Yuandong; Wang, Ruikang K; Iliff, Jeffrey J; Alkayed, Nabil J
Local blood flow in the brain is tightly coupled to metabolic demands, a phenomenon termed functional hyperemia. Both capillaries and arterioles contribute to the hyperemic response to neuronal activity via different mechanisms and timescales. The nature and specific signaling involved in the hyperemic response of capillaries versus arterioles, and their temporal relationship are not fully defined. We determined the time-dependent changes in capillary flux and diameter versus arteriolar velocity and flow following whisker stimulation using optical microangiography (OMAG) and two-photon microscopy. We further characterized depth-resolved responses of individual capillaries versus capillary networks. We hypothesized that capillaries respond first to neuronal activation, and that they exhibit a coordinated response mediated via endothelial-derived epoxyeicosatrienoates (EETs) acting on pericytes. To visualize peri-capillary pericytes, we used Tie2-GFP/NG2-DsRed mice, and to determine the role of endothelial-derived EETs, we compared cerebrovascular responses to whisker stimulation between wild-type mice and mice with lower endothelial EETs (Tie2-hsEH). We found that capillaries respond immediately to neuronal activation in an orchestrated network-level manner, a response attenuated in Tie2-hsEH and inhibited by blocking EETs action on pericytes. These results demonstrate that capillaries are first responders during functional hyperemia, and that they exhibit a network-level response mediated via endothelial-derived EETs' action on peri-capillary pericytes.